2014
DOI: 10.17795/intjsh-18906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Correlation between BMI, Waist Circumference, and the Snacking Pattern and Dairy Consumption among Female Student Residents of Shiraz University Dormitories

Abstract: Background:It is suggested that the type and frequency of snacks as well as dairy consumption can influence body weight and composition. Objectives: This study attempts to assess the correlation of BMI and waist circumference with snacking pattern and dairy consumption among female university students. Materials and Methods: We randomly selected 112 female students who were residents of Shiraz University dormitories as participants in this cross-sectional study. Weight, height and waist circumference of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Even though the relationship between snacking and obesity or abdominal obesity is not clear, some studies have found that the increased consumption of energy-dense, high-sugar, high-fat meals, snacking has been regarded one of the key factors to obesity (44). Other studies failed to establish the relationship between snacking and obesity or abdominal obesity (45). This is because the type of snack practicedmatters.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the relationship between snacking and obesity or abdominal obesity is not clear, some studies have found that the increased consumption of energy-dense, high-sugar, high-fat meals, snacking has been regarded one of the key factors to obesity (44). Other studies failed to establish the relationship between snacking and obesity or abdominal obesity (45). This is because the type of snack practicedmatters.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the relationship between snacking and obesity or abdominal obesity is unclear, some studies have suggested that consumption of energy-dense, high-sugar, high-fat snacks is a key factor in obesity [ 51 ]. Other studies failed to establish a relationship between snacking and obesity or abdominal obesity [ 52 ]. This may be because the type of snack eaten matters.…”
Section: Discussionmentioning
confidence: 99%